DAMPAK GAME ONLINE TERHADAP PERILAKU MORAL PESERTA DIDIK DI KELURAHAN PAPPA KECAMATAN PATTALLASSANG KABUPATEN TAKALAR - Sri Nadira Ahmad; Andi Aco Agus; Lukman Ilham (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2022)
Abstract. This study aims to determine: (1) The consequences of the habit of playing online games on the behavior of students in the household environment (2) The efforts of parents in overcoming the negative impact of student behavior from playing online games. This study uses a qualitative approach which is analyzed and written descriptively. Data collection techniques were carried out using observation, interviews, and documentation methods involving as many as 20 (twenty) informants consisting of students and parents. The results of this study indicate that: (1) Online games affect the daily lives of students indirectly, this can be seen through the consequences arising from the habit of playing online games in the family household environment in Pappa Village, Pattallassang District, Takalar Regency including: (a) behavior emotional or speaking impolitely, (b) being dishonest or lying, (c) sleeping when school is online (online), (d) neglecting prayers, and (e) not caring about the surrounding environment. (2) Parental efforts in overcoming the negative impact of student behavior from playing online games in Pappa Village, Pattallassang District, Takalar Regency, are carried out through (a) parental supervision, (b) providing advice to children, (c) tightening rules at home, and (d) cooperation between the school and parents. This paper is expected to help in efforts to overcome online game addiction. Furthermore, future research needs to examine in depth other alternatives for the negative impact of online games.